Titanium toxicity-A review - R Venkat Raghavan; Anil Melath; K Subair; T P Mohammed Feroz (Journal of Multidisciplinary Dental Research)
Titanium is a commonly used inert bio-implant material within the medical and dental fields. Although the use of titanium is thought to be safe with a high success rate, in some cases, there are rare reports of problems caused by titanium. Even though various recent advancement in the implant has been implicated in this era, still titanium is gold stranded among dental implant materials. In most of these problematic reports, only individual reports are dominant and comprehensive reporting has not been performed. This comprehensive article has been prepared to review the toxicity of titanium and its alloy materials in the field of dentistry. Keywords: Allergy; implant toxicity; titanium implants; titanium particles; Yellow nail syndrome